(untitled) (Journal of Foreign Language Studies, 2020)
This study investigates the impacts of Anki, a web-based flashcard program, on learners’ vocabulary learning and their perceptions towards the program based on three criteria: usefulness, convenience and satisfaction. Participants from two intact classes at elementary level were included in the study. Both groups underwent a pre-test and then participated in a 3-week course to learn the KET Vocabulary List developed by Cambridge TESOL (CEFR level A2). The control group (n = 18) utilized traditional paper flashcards while the experimental group (n = 18) used Anki flashcards. They then took a post-test so that comparisons between these two methods could be drawn. The results showed that both methods would facilitate learners’ vocabulary learning; however, the experimental group had better performance than the control one. Therefore, it can be concluded that Anki is an effective tool for language learners to improve their vocabulary.